PLIOCENE MOLLUSCS TAXONOMIC DIVERSITY AS A TOOL FOR THE CLIMATIC-OCEANOGRAPHIC RECONSTRUCTION AND STRATIGRAPHY. TWO EXAMPLES FROM THE EASTERN MEDITERRANEAN - Koskeridou, E. (Bulletin of the Geological Society of Greece, 2006)
Due to their high extinction rate, the Molluscs of the Pliocene in the Mediterranean, resulted potentially useful as a tool for climatic-oceanographic and chronological inferences. In the present study, we document the possibility of application of the model of Raffi and Monegatti (1993) in the region of Eastern Mediterranean, by studying two examples from the Hellenic area and Cyprus. This model concerns the extinction events of Molluscs of Pliocene, separating 4 different units of Molluscs with different climatic-oceanographic importance. It is documented that the two selected sections, Atsipades in central Crete and Athienou in southern Cyprus, give elements for the correlation of their deposits with this model. The Atsipades section is connected with the first significant extinction event, at the Mollusc Units of Raffi and Monegatti, resulting from the first important Pliocene cooling phenomenon of our hemisphere. The Athienou section is connected with the MPMU2 unit of Raffi and Monegatti, between the first and second distinctive extinction events of the Pliocene Molluscs.